PUBLIC VALUES OF THE IMPLEMENTATION OF THE E-PAKLADI APPLICATION TO REALIZE E GOVERNANCE IN BEJI VILLAGE (CASE STUDY AT THE BEJI PASURUAN VILLAGE HALL) - Tohirin, Muchammad Shobakhut; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to describe the public value of the implementation of the E-PAKLADI application in supporting the implementation of e-governance in Beji Village, Pasuruan Regency. The research background is based on the need to improve the efficiency, transparency, and accountability of population administration services through digital innovation at the village level. Method: The research was conducted using a descriptive qualitative method using the purposive sampling technique of relevant informants, and data collection was obtained through observation, interviews, and documentation analyzed using the Miles & Huberman mode approach. Results: Based on the results of the research, it was obtained that first, from the aspect of legitimacy and support, the E-PAKLADI program has a strong legal basis and infrastructure support from the village government. Second, from the aspect of operational capabilities, this application is effective in facilitating access to services and increasing transparency, although there are still obstacles such as network disruptions and application maintenance. Third, from the aspect of substantial value, E-PAKLADI is able to improve administrative efficiency, strengthen community participation, and minimize administrative errors through digitalization. Novelty: The novelty of this research lies in the comprehensive analysis of the application of the public value framework of O'Flynn in the context of villages, which shows that the success of digital innovation is not limited to the use of technology alone, but also to legitimacy, resource support, and community acceptance.